Developing cognate awareness through pedagogical translanguaging. Issue 8 (14th September 2022) - Cenoz, Jasone; Leonet, Oihana; Gorter, Durk
ABSTRACT: This article is on pedagogical translanguaging, understood as planned instructional strategies used with a pedagogical purpose in a multilingual educational context. The paper reports a study on cognate identification and cognate awareness carried out in a multilingual primary school. The study aims at analyzing whether the identification of cognates in three languages is related to linguistic factors and to teaching. The relationship between teaching cognates and metalinguistic awareness is also explored. Half of the participants took part in an intervention based on pedagogical translanguaging using multilingual resources from the students' own repertoire while the other half followed regular classes. Participants completed a background questionnaire and a cognate recognition task. Information was also gathered by means of a think-aloud protocol and an interview. The results indicate that the identification of cognates is connected to the linguistic characteristics of cognates but not to having Basque or Spanish as a first language. Participants who had taken part in the intervention showed a higher development of cognate awareness but there were no significant differences between the groups in cognate identification. The results are exploratory but they indicate that using the languages in the students' whole linguistic repertoire can create more opportunities for language learning.